Analisis implementasi kebijakan Sistem Kesehatan Pertahanan Negara (Siskeshanneg) menghadapi ancaman faktual pandemi COVID-19 di Lembaga Kedokteran Gigi (Ladokgi) Raden Eddy MartadinataAnalysis of the National Defense Health System (Siskeshanneg) policy implementation on the Covid-19 pandemic factual threat at Raden Eddy Martadinata Naval Dentistry Institute (Ladokgi) - Sugeng Winarno; Ganesha Wandawa; Suhardjo Sitam (Padjadjaran Journal of Dental Researchers and Students, 2021)
ABSTRAK Pendahuluan: Sistem Kesehatan Pertahanan Negara (Siskeshanneg) adalah totalitas sumber daya bidang kesehatan yang dapat digunakan secara terarah dan terpadu untuk menghadapi ancaman bidang kesehatan. Pandemi COVID-19 merupakan manifestasi ancaman bidang kesehatan yang memerlukan Siskeshaneg untuk menghadapinya. Hingga saat ini implementasi kebijakan ini masih terjadi permasalahan sehingga mempengaruhi kesiapsiagaan institusi dalam menghadapi suatu bencana. Tujuan penelitian ini adalah untuk memberikan gambaran tentang proses implementasi kebijakan Siskeshanneg di Ladokgi Raden Eddy Martadinata (Ladokgi REM) ini dilihat dari empat aspek yang mengacu pada analisis implementasi model Edward III. Metode: Penelitian menggunakan metode deskriptif kualitatif. Pengumpulan data melalui wawancara mendalam, observasi dan penelaahan dokumen. Pemilihan informan melalui teknik purposive sampling. Validasi data dilakukan triangulasi terhadap sumber, metode dan teori. Hasil: Gambaran proses implementasi Siskeshaneg di Ladokgi REM memperlihatkan komunikasi menggunakan jaring fungsi komando, sumberdaya bidang personel kekuatannya berkurang, bidang anggaran dilakukan refocusing pada kegiatan terkait penanggulangan COVID-19, pemenuhan sarana dan prasarana ruangan sesuai protokol kesehatan dan pembagian zonasi, struktur birokrasi tidak terfragmentasi serta disposisi pimpinan dan anggota berkomitmen penuh dan sesuai perintah. Faktor penghambat meliputi penyiapan sarana dan prasarana membutuhkan waktu 3 bulan, kecemasan pada sebagian anggota dan pasien takut terpapar COVID-19. serta harga logistik kesehatan yang melambung. Simpulan: Implementasi Siskeshaneg di Ladokgi REM dapat berjalan baik, dengan indikator keberhasilan berupa kecepatan pengambilan keputusan, kepemimpinan dan kemampuan adaptasi sehingga kegiatan layanan kesehatan dapat terselenggara di masa pandemi COVID-19.Kata kunci: implementasi kebijakan; Siskeshanneg; ancaman faktual; pandemi COVID-19 ABSTRACTIntroduction: The National Defense Health System (Siskeshanneg) is the totality of health sector resources that can be used in a directed and integrated manner to deal with threats in the health sector. The COVID-19 pandemic manifests a health sector threat that requires the National Defense Health System implementation. However, until now, the implementation of this policy is still experiencing problems that affect institutions' preparedness in the face of a disaster. The purpose of this study was to provide an overview of the implementing process of the National Health Defense System (Siskeshanneg) policy at Raden Eddy Martadinata Naval Dentistry Institute (Ladokgi REM) observed from four aspects that refer to the analysis of the Edward III model implementation. Methods: The study used a qualitative descriptive method. Collecting data through in-depth interviews, observation and document review. Selection of informants through purposive sampling technique. Data validation was carried out by triangulation of sources, methods, and theories. Results: An overview of the National Defense Health System implementation process in Raden Eddy Martadinata Naval Dentistry Institute shows that communication was performed through command function network; personnel resources were reduced in strength; the budget aspect was refocused on activities related to COVID-19 prevention; fulfilment of room facilities and infrastructure according to health protocols and zoning distribution; the bureaucratic structure has not fragmented, and the disposition of leaders and staffs was fully committed and according to orders. Inhibiting factors included preparing facilities and infrastructure that take three months, some staff and patients' anxiety about being exposed to COVID-19, and soaring health logistics prices. Conclusions: Implementing the National Health Defense System (Siskeshanneg) policy at Raden Eddy Martadinata Naval Dentistry Institute is thriving, with indicators in the form of fast decision-making, leadership, and adaptability for health service activities were able to be carried out during the COVID-19 pandemic.Keywords: policy implementation; National Defense Health System; factual threats; COVID-19 pandemic